(untitled) (Development Engineering Conferences Center Articles Database, 2025)
Artificial intelligence (AI) has been revolutionizing the medical field at an increasing pace in recent years. The objectives of AI applications in the medical field are to improve accuracy and enhance efficiency in the treatment of various medical conditions. AI models and applications such as ML, deep learning (DL), natural language processing (NLP), reinforcement learning (RL), and generative models are proving to be of immense benefit in predicting medical conditions and managing their treatment. The applications of AI in the medical field will be elaborated upon in this study through the use of ML and DL in medical imaging studies, the application of NLP in processing clinical texts, and the implementation of RL in the treatment of various medical conditions. The combined effect of AI and IoMT, along with predictive analytics, will also allow doctors to monitor patients in real-time and take proper anticipations in the treatment of medical conditions. AI’s role in genomic medicine, along with the management of hospitals and the efficient utilization of medical resources, will also be described. The evolving medical practices through AI will enable doctors to provide more efficient and patient-centric medical treatment in the coming years. The study will also discuss the challenges faced by AI regarding the concerns of the patients’ confidentiality of medical information and the need to be transparent in decision-making. The emerging trends of AI will be of immense benefit to the medical field in providing efficient medical practices in the coming years.